2011
DOI: 10.1080/09674845.2011.11730324
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori: association with gall bladder disorders in Pakistan

Abstract: Helicobacter species colonise the biliary tract and therefore this study explores the relationship between of Helicobacter pylori and cholecystitis. Bile and gall bladder tissue samples were obtained from 144 patients who underwent cholecystectomy. Of these, 89 had chronic cholecystitis with cholelithiasis, 44 had gall bladder carcinoma and 11 had gall bladder polyps. Histopathology examination included special staining and immunohistochemistry (IHC), while Helicobacter species (H. pylori, H. bilis and H. hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…The strategy of study selection is displayed in Figure S1. Eighteen case-control studies published between 1998 and 2011 were finally eligible for meta-analysis (Table 1) [8], [9], [22][37]. These studies involved 1678 patients with a total Helicobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…The strategy of study selection is displayed in Figure S1. Eighteen case-control studies published between 1998 and 2011 were finally eligible for meta-analysis (Table 1) [8], [9], [22][37]. These studies involved 1678 patients with a total Helicobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…Helaly and colleagues showed that H. pylori is present in almost 40.9% of samples in patients with chronic calcular cholecystitis [23]. Similarly, Yakooband and colleagues demonstrated that 22 (25%) patients in case group and 5 (9%) in controls were positive for H. pylori [20]. Other findings were also indicative of the positive association between H. pylori infection and cholecystitis, where the association varied from 7% to more than 55% [21,22].…”
mentioning
confidence: 82%
“…But the results are contradictory. Some studies clearly show a significant association between positive H. pylori test in the stomach and the presence of stones in the gallbladder [20][21][22]. Studies also suggest that infection by this organism in the gallbladder can be considered as an etiologic factor in the formation of gallstones, especially pigment stones [23].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of Helicobacter in gallbladder tissue histology varies 40 from 0 % to 28 % [1][2][3][4][5][6]. BostanoAylu et al [1] could not culture Helicobacter in any of their 47 patients with gallstone disease and 30 controls.…”
mentioning
confidence: 99%
“…Indirect evidence of H. pylori in gallbladder by demonstration of DNA of different components of bacillus is found in 7 % to 61.5 % tissue examined [2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%